2008
DOI: 10.1111/j.1365-2710.2000.00302.x
|View full text |Cite
|
Sign up to set email alerts
|

Sequential improvement of anxiety, depression and anhedonia with sertraline treatment in patients with major depression

Abstract: Objective: To establish the therapeutic effect pro®le of sertraline in major depression. It was hypothesized that the antidepressant effect of sertraline showed three phases: Phase 1 where improvements in anxiety are most pronounced; Phase 2 where the greatest improvements are in depressive symptoms; and Phase 3 where the symptoms of anhedonia show the most improvement. To test this hypothesis, an 8-week, openlabel study was conducted. Methods: Patients with a major depressive episode (DSM-IV) and a score ³24 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 25 publications
0
11
1
Order By: Relevance
“…These results are somewhat at odds with the summary of symptom trajectories described earlier by Boyer et al , Chekroud et al , or by Kasahara et al . Boyer et al's depression cluster contained symptoms of insomnia, fatigability, and psychomotor retardation, while their hedonic cluster included those of suicidal thoughts and anhedonia; if our observation of individual criterion symptoms were correct, it would mean that their clusters contained symptoms of fast and slow recovery and may well have been unable to detect important differences among them. The situation is similar for Chekroud et al's observation.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“…These results are somewhat at odds with the summary of symptom trajectories described earlier by Boyer et al , Chekroud et al , or by Kasahara et al . Boyer et al's depression cluster contained symptoms of insomnia, fatigability, and psychomotor retardation, while their hedonic cluster included those of suicidal thoughts and anhedonia; if our observation of individual criterion symptoms were correct, it would mean that their clusters contained symptoms of fast and slow recovery and may well have been unable to detect important differences among them. The situation is similar for Chekroud et al's observation.…”
Section: Discussioncontrasting
confidence: 80%
“…Only a few studies have followed the course of individual symptoms of depression through the acute phase treatment; for example, Boyer et al observed that anxiety disappeared first, followed by depression, then by anhedonia under the eight‐week treatment with sertraline . Chekroud et al observed that the trajectories of core emotional symptoms of depression showed faster reduction than those of sleep symptoms, which in turn showed faster improvement than those of atypical symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, and in line to the mode of action of SSRI, a study with sertraline administered to depressed patients showed that depression and anxiety responded earlier to the antidepressant than the improvement of anhedonia (Boyer, Tassin, Falissart, & Troy, 2000).…”
Section: This Data Show and Confirm How Agomelatine Effect Is Indepenmentioning
confidence: 99%
“…In-depth measurement of hedonic capacity along with the measurement of mood and behavior is important in depression treatment studies (Boyer, Tassin, Falissart, & Troy, 2000). Self-administered assessments may not be sufficient, particularly in severe psychiatric conditions.…”
Section: Discussionmentioning
confidence: 99%